Técnicas grafo plásticas y las relaciones lógico matemáticas en los niños de inicial ll de la Escuela de Educación Básica Dr. Edison Calle Loaiza de la ciudad de Loja, periodo 2022-2023. - Carrión Abad, Angie Valentina (2024)
Logical-mathematical relationships indicate the development of cognitive abilities related to logic and mathematics in this stage of childhood, children are beginning to acquire a basic understanding of numerical concepts, classification, seriation and spatial relationships, since it allows them to analyse and comprehend their surrounding world. The main objective of this research work is to determine how graph-plastic techniques strengthen logical-mathematical relationships in children of initial II at the Dr. Edison Calle Loaiza Basic Education School in the city of Loja, period 2022-2023. Also, the research was framed in a quasi-experimental design, under a mixed approach, with a descriptive scope, also we included the methods: inductive-deductive and analytical-synthetic, for the research’s development. A checklist was also used to record the progress and important observations throughout the investigation. We worked with a sample of 32 children, in which a pre- and post-test was applied by means of the basic mathematical competency test 3 (TEMA-3), thus evidencing that 82% of the children were placed in the poor and very poor indicators, since they had difficulty in enumerating from 1 to 5, cardinality rule, nonverbal addition and subtraction, counting from 1 to 10, show fingers up to 5; while 18% fell in the below average indicator, after the intervention, 53% were located in the poor and very poor indicator, while 47% reached the below average one. Finally, the grapho-plastic techniques are an interesting strategy in which children, through the manipulation of materials, acquire the learning of basic contents, by means of techniques such as moulding, painting, punching, etc., being feasible to work with numbers, colours, geometric figures, serialization, among others, ensuring that they acquire significant learning. Keywords: Mathematical concepts, moulding, punching, reasoning, techniques.